Modernization of commutation devices and an improvement of main parameters of the UTR-2 radio telescope - Zakharenko, V.V.; Sharykin, N.K.; Rudavin, E.R. (Кинематика и физика небесных тел, 2005)
The paper describes the results of modernization of the calibration system commutation devices and a check of pattern parameters of the UTR-2 radio telescope. As a result of the modernization an effective area of the telescope has been increased by 23 percent. In a frequency range from 20 to 32 MHz an improvement in sensitivity more than 1.2...1.5 dB has been obtained. On the lower end of the UTR-2 operating frequency range (from 8 to 12 MHz) the interference immunity has been increased by 10 dB.